A Homogenous, Photocrosslinkable Poly(dimethylsiloxane‐co‐methylvinylsiloxane) Solution in an Acrylate Monomer. Issue 1 (11th October 2022) - Park, Seung Koo; Park, Bong Je; Shin, Eun Jin; Choi, Meejeong; Park, Suntak; Shin, Hyung Cheol
Abstract: In this study, a simple photocuring method is proposed for preparing PDMS elastomers using a homogenous poly(dimethylsiloxane) (PDMS) solution in tert ‐butyl acrylate ( t BA) as an alternative way of mechanically blending two kinds of PDMS respectively containing vinyl and hydridosilyl groups over a platinum catalyst. Poly(dimethylsiloxane‐ co ‐methylvinylsiloxane) (PDMSc) with 30 mol% of vinyl moieties is synthesized. The functionalized PDMS is estimated to be soluble in t BA from theoretical calculations of solubility parameters of PDMS and several liquid monomers. The PDMS solution is satisfactorily photocured under a conventional photoinitiator. Initial modulus and strain of the photocured films increase from 144 to 552 MPa and decrease from 3.96 to 1.84, respectively, as the t BA content rises from 5 to 30 wt%. They are extremely transparent in a visible region ( T > 94%) regardless of the amount of t BA. The unreacted vinyl groups in PDMSc are inter‐ or intrareacted near 200 °C and γ ‐hydrogen transfer reactions from the tert ‐butyl groups in poly( tert ‐butyl acrylate) occur over 250 °C. One of the photocrosslinked films exhibits outstanding performance as an electroactive polymer in application. In essence, this study will initiate a new methodological research into provision of PDMS elastomers using an easily formulated photocrosslinkable PDMS solution. Abstract : A homogenous, photocrosslinkable poly(dimethylsiloxane) (PDMS) solution in tert ‐butyl acrylate ( t BA) is developed. PDMS is highly functionalized to be readily crosslinked upon UV‐irradiation. t BA acts as a crosslinker as well as a solvent suitable for the PDMS. Photocured films can be successfully obtained from the PDMS solution over a simple fabrication process. Their physical properties meet expectations of using as an elastomer material.